AN EVALUATION OF ISIZULU LITERACY DEVELOPMENT IN LOWER GRADES: THE IMPACT OF LANGUAGE POLICIES - Berger, Sophie; Fischer, Lucas (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The development of literacy in African languages in South African schools has been a longstanding challenge despite legislative frameworks intended to facilitate it. This study investigates the use of isiZulu, an indigenous African language, as a medium for literacy development in selected primary and intermediate schools in KwaZulu-Natal province. The study examines language policies in the schools and to what extent they promote isiZulu literacy development. The findings reveal prevalent inadequacies in language policies, educational resources and the predominantly English medium of instruction, which exclude isiZulu development. Consequently, the study recommends the prioritization of African language literacy development in school language policies, and the need for population-focused initiatives to support this approach